Socio-economic Factors and Land Degradation: Mediterranean Perspectives - Salvati, Luca; Forino, Giuseppe; Zitti, Marco (Annals of Arid Zone, 2016)
Land degradation is a complex phenomenon determining natural resources deterioration that claims for multi-dimensional and multi-scale policies targeting the sustainability of socio-economic development. Mediterranean-type ecosystems are identified as hotspots for land degradation due to the dynamic interplay between climatic change and increasing human pressure on land. However, while the role of population growth, wealth, and policies is still ambiguous, socio-economic disparities are considered an important factor shaping the vulnerability to degradation of Mediterranean land. Territorial disparities determined gaps in the availability of natural capital, increasing rural poverty, and unsustainable management of soil and water especially under climate change scenarios. Understanding the intimate, two-sided relationships between territorial disparities and land degradation is therefore a deserving issue that may inform policies with the final aim to reduce desertification vulnerability and improve socio-economic conditions of local communities. Key words: Desertification, local economy, social disparities, Sustainable development, Mediterranean Europe.